Pengembangan Media Pembelajaran IPAS Flashcard Barcode untuk Meningkatkan Hasil Belajar SD Negeri Sadeng 02 Semarang - Ananta, Yosrifal Bima Galih; Isdaryanti, Barokah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
The low learning outcomes and limited use of contextual, technology-based instructional media in elementary schools underscore the need for innovative, effective, and engaging learning tools. This study aims to develop, assess the feasibility of, and evaluate the effectiveness of Flashcard Barcode media supported by Augmented Reality (AR) for teaching the topic of Indonesia’s Cultural Diversity to fourth-grade students at SD Negeri Sadeng 02, Semarang City. The research employed a Research and Development (R&D) approach using the ADDIE model and a quasi-experimental one-group pretest-posttest design. The study involved 24 students, divided into a small-scale trial group (4 students) and a large-scale trial group (20 students). Data were collected through interviews, observations, questionnaires, and learning outcome tests. Validation results indicated a media feasibility score of 92% and a material feasibility score of 90%, both categorized as “highly feasible.” Effectiveness testing showed a significant increase in posttest scores, with mastery learning reaching 100% in the small-scale trial and 95% in the large-scale trial. The T-test yielded a significance value of 0.00 (<0.05), and the N-Gain analysis reached 72.26% (small-scale) and 71.29% (large-scale). The study concludes that AR-based Flashcard Barcode media is effective in enhancing student learning outcomes. The findings highlight the importance of integrating interactive, visually driven technology into elementary science and social studies (IPAS) instruction to improve student engagement and comprehension. Keywords: Interactive Learning Media; Augmented Reality; Flashcard Barcode; Indonesia’s Cultural Diversity; Student Learning Outcomes